Application of multiplex arrays for cytokine and chemokine profiling of bile. Issue 1 (May 2015) - Kemp, Troy J.; Castro, Felipe A.; Gao, Yu-Tang; Hildesheim, Allan; Nogueira, Leticia; Wang, Bing-Sheng; Sun, Lu; Shelton, Gloriana; Pfeiffer, Ruth M.; Hsing, Ann W.; Pinto, Ligia A.; Koshiol, Jill
Highlights We evaluated the performance of 69 analytes in bile with multiplex assays. Most analytes can be reliably measured from bile and used in epidemiologic studies. Both bead-based and planar multiplex assays were utilized for select analytes. Technology may aid in identifying critical markers associated with gallbladder cancer.